Impact of Shrimp Ponds on Mangrove Blue Carbon Stocks in Ecuador - Jéssica Merecí-Guamán (Forests, 2021)
Mangrove forests play an important role in mitigating climate change but are threatened by aquaculture expansion. The inclusion of mangroves in climate change mitigation strategies requires measuring of carbon stocks and the emissions caused by land use change over time. This study provides a synthesis of carbon stocks in mangrove and shrimp ponds in the Gulf of Guayaquil. In this study area, we identified 134,064 ha of mangrove forest and 153,950 ha of shrimp farms. Two mangrove strata were identified according to their height and basal area: medium-statured mangrove (lower height and basal area) and tall mangrove (greater height and basal area). These strata showed statistical differences in aboveground carbon stocks. In both strata, the most abundant mangrove species was Rhizophora mangle. For both strata, trees had a maximum height (>30 m), and their density was greater than 827 ha−1. Total ecosystem level carbon stocks (measured to 1 m soil depth) were 320.9 Mg C ha−1 in medium-statured mangroves and 419.4 Mg C ha−1 in tall mangroves. The differences are attributable to higher basal area, soil organic carbon concentrations and salinity, tidal range, origin of allochthonous material, and herbivory patterns. Mangrove soils represented >80% of the total ecosystem carbon. Ecosystem carbon stocks were lower (81.9 Mg C ha−1) in the shrimp farms, 50% less than in undisturbed mangroves. Our results highlight mangroves as tropical ecosystems with extremely high carbon storage; therefore, they play an important role in mitigating climate change. This research provides a better understanding of how carbon stocks in this gulf are found and can be used for design strategies to protect global natural carbon sinks.